Tensiones jurisprudenciales en la pensión compartida entre esposa y compañera (2021)
The present work was proposed as an objective: to identify the existing jurisprudential tensions between the Wife and the partner in the shared pension in Colombia, the above understood understood, that as a consequence of the issuance of Law 797 of 2003, by which they are reformed some provisions of the general pension system provided for in Law 100 of 1993 and provisions are adopted on the excepted and special Pension Regimes, the legislator established the primacy of the formal link over the material in relation to access to the survivor's pension, leaving no protection of the permanent partner in cases of shared coexistence, the issue has been prolifically examined by national jurisprudence, from which two antagonistic theses have resulted, the constitutionalist thesis that defends the principle of family equality, and the legalistic thesis that promotes a literal and radical interpretation of the norm, this antagonism generating a clash of t between different jurisprudence, to this end, this document will confront the different points of view and highlight the importance of the constitutional thesis.